Antimicrobial Resistance and Anti-Biofilms - Liu, Junyan; Chen, Ding-Qiang; Tan, Yulong; Gan, Ren-You; Qu, Guanggang; Xu, Zhenbo (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint is based on "Antimicrobial resistance and anti-biofilms" in the journal Antibiotics since November of 2020. This reprint has one editorial article, eight research articles, one review article, and one case report article, covering a time period of 15 months from December of 2021 to February of 2023. Containing three major sub-topics in this reprint, four manuscripts regarding the prevalence of resistant microbes, the emergence and evolution of resistance, and the molecular investigation of resistance mechanisms fall into the first sub-topic as "Antimicrobial resistance in microorganisms: epidemiology and molecular mechanism"; three manuscripts fall into the second sub-topic as "New antibiofilm strategy against fungal and/or bacterial biofilms"; and three manuscripts regarding the production and characteristics of these functional material encapsulated/ delivered natural compounds, in vitro and in vivo antimicrobial and antivirulent effects, and their potential applications, such as in food and medicine, fall into the third sub-topic as "Influence of Functional Material-Based Encapsulation/Delivery on the Antimicrobial and Antivirulent Effects of Natural Compounds". Articles contained in this reprint have provided comprehensive knowledge and insight in understanding of antimicrobial resistance epidemiology and molecular mechanism and new antibiofilm strategies.